2021
DOI: 10.3389/fcell.2021.767283
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Expression Profiles and Bioinformatic Analysis in Mouse Models of Obstructive Sleep Apnea-Induced Cardiac Injury: Novel Insights Into Pathogenesis

Abstract: Circular RNAs (circRNAs) participate in the development of various kinds of diseases. However, the function and roles of circRNAs in obstructive sleep apnea (OSA)-induced cardiovascular disease remain poorly understood. Therefore, we sought to explore the circRNA expression profiles and predict their functions in OSA-induced cardiac injury with the use of bioinformatics analysis. The model of OSA was established in mouse treated by chronic intermittent hypoxia (CIH) exposure. Then, we screened the circRNA prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…An CIH model was established by chronic intermittent hypoxia (IH) as previously described by us [ 3 , 10 ]. Briefly, we used the intermittent hypoxia system to create a CIH environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An CIH model was established by chronic intermittent hypoxia (IH) as previously described by us [ 3 , 10 ]. Briefly, we used the intermittent hypoxia system to create a CIH environment.…”
Section: Methodsmentioning
confidence: 99%
“…OSA is a common condition with major cardiovascular consequences. At present, a great deal is known about the role of OSA in cardiovascular diseases such as myocardial infraction [ 2 ] and cardiac injury [ 3 ]. Previous studies show that severe OSA is a risk factor for abnormal liver enzymes and steatohepatitis independent of overweight states [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mice were randomly divided into two groups: the CIH group and the control group. The CIH mouse model was established as described in our previous study ( Lai et al, 2021 ). In brief, the mice were placed in cages with a gas control system, which regulated nitrogen, air, and oxygen flow into the chambers.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is reported that the occurrence of OSAS is not only induced by simple airway obstruction, but also associated with upper airway collapse and disorders in respiratory central nervous regulatory factor. 4 Activation of systemic inflammation is considered as one of the major mechanisms in the pathogenesis of OSAS, and increased inflammatory cytokines are observed in OSAS progression. 5 It is noticed that obesity is also closely related with the presence of OSAS, and about 70% OSAS patients had obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The direct pathogenesis of OSAS is the stenosis and obstruction of the upper airway. However, it is reported that the occurrence of OSAS is not only induced by simple airway obstruction, but also associated with upper airway collapse and disorders in respiratory central nervous regulatory factor 4 . Activation of systemic inflammation is considered as one of the major mechanisms in the pathogenesis of OSAS, and increased inflammatory cytokines are observed in OSAS progression 5 .…”
Section: Introductionmentioning
confidence: 99%